Growth and feed utilization potentials of local chicken ecotypes in Ethiopia - Dessie, Tadelle; Tadesse, M.; Peters, Kurt J. (2005)
Growth and feed utilisation potentials of six chicken populations were evaluated at Debre Zeit Agricultural Research Centre, Ethiopia. Five local chicken ecotypes originated from different Agro-ecologies namely, Tilili, Horro, Chefe, Jarso and Tepi were included. In this study, Fayoumi chicken breed originated from Egypt was used as a reference breed. Ecotype had a significant (p<0.01) effect on overall body weight gain per bird and mean body weight gain per bird per day from day old to 6 weeks of age. The highest body weight gain per bird was recorded for Fayoumi chicks. The Fayoumi chicks were 12, 98 and 49% heavier than chicks from Chefe ecotype, Jarso ecotype and mean daily body weight gain of all local ecotypes, respectively, at six weeks of age. Chefe chicks showed 77% positive deviation over chicks from Jarso market sheds in terms of total body weight gain per bird in this age. The result from the analysis of variance showed a highly significant (p<0.001) difference on all traits considered among the different ecotypes and sex from six to 12 weeks of age. The highest body weight gain per bird and mean body weight gain/bird/day among the locals were recorded for Tilili growers. The Fayoumi chicks were 28, 77 and 52% heavier than chicks from Tilili ecotypes, Tepi ecotypes and mean body weight gain of all local ecotypes, respectively. Male growers from Tilili ecotype, Tepi ecotype and mean body weight gain of all local ecotypes, were 22, 30 and 33% highest in body weight gain per bird over female chicken at twelve weeks of age, respectively. Feed conversion ratio was also significantly (p<0.01) affected by ecotypes. The highest feed requirement per unit gain was recorded for the Fayoumi chicks followed by chicks from Tepi and Horro chicks. However, the lowest feed requirement per units of gain was recorded for Tilili and Chefe chicks with feed conversion ratio of 4.9g and 5.2g feed per unit of gain, respectively. From the results of this study it is possible to conclude that the growth and feed utilization performances of ecotypes studied underlines the rather large difference between ecotypes with some exhibiting a remarkably higher performance levels.